Important requirements for desorption/ionization mass spectrometric measurements of temozolomide-induced 2′-deoxyguanosine methylations in DNA - Fresnais, Margaux; Jung, Ina; Klein, Uli B.; Miller, Aubry K.; Turcan, S̨evin; Haefeli, Walter E.; Burhenne, Jürgen; Longuespée, Rémi (Cancers, 2023)
In clinical pharmacology, drug quantification is mainly performed from the circulation for pharmacokinetic purposes. Finely monitoring the chemical effect of drugs at their chemical sites of action for pharmacodynamics would have a major impact in several contexts of personalized medicine. Monitoring appropriate drug exposure is particularly challenging for alkylating drugs such as temozolomide (TMZ) because there is no flow equilibrium that would allow reliable conclusions to be drawn about the alkylation of the target site from plasma concentrations. During the treatment of glioblastoma, it appears, therefore, promising to directly monitor the alkylating effect of TMZ rather than plasma exposure, ideally at the site of action. Mass spectrometry (MS) is a method of choice for the quantification of methylated guanines and, more specifically, of O6-methylguanines as a marker of TMZ exposure at the site of action. Depending on the chosen strategy to analyze modified purines and 2′-deoxynucleosides, the analysis of methylated guanines and 2′-deoxyguanosines is prone to important artefacts due to the overlap between masses of (i) guanines from DNA and RNA, and (ii) different methylated species of guanines. Therefore, the specific analysis of O6-methyl-2′deoxyguanosine, which is the product of the TMZ effect, is highly challenging. In this work, we report observations from matrix-assisted laser desorption/ionization (MALDI), and desorption electrospray ionization (DESI) MS analyses. These allow for the construction of a decision tree to initiate studies using desorption/ionization MS for the analysis of 2′-deoxyguanosine methylations induced by TMZ.
Gesehen am 29.03.2023
Keywords: Temozolomid